Characterization of Landslide geometry using Seismic Refraction Tomography in the GayoLues, Indonesia - Muzakir Zainal; Badrul Munir; Marwan Marwan; Muhammad Yanis; Akmal Muhni (Diponegoro University Semarang Indonesia, 2021)
Landslides are the most common geological phenomenon in Indonesia.The event is damage to public infrastructure, and fatalities was a big impact. Therefore, mapping the geometry of landslides is a part of the mitigation effort possible by geophysical methods. In this research, we applied seismic refraction tomography (SRT) to study the geometry of the sliding zone from the landslide event.TheNational Disaster Management Authority reported that the area was frequently occurring landslide disaster, i.e. 2018, 2019 and 2020 which caused the public infrastructure and obstructed the road access from the central to the west of Aceh. The SRT was measured in two profileslong the road.Data measurements were conducted on the side of the Babahrot - GayoLues road section that had experienced landslides.Measurements were made using the Seismograph PASI 16S24-P and 24 geophones to obtain a 92-meterlong profile with 2 meter spacing between the geophones. P-wave velocity data modeling is done using ZondST2D software.The results of modeling profiles 1 and 2 describe three different subsurface layers.The SRT profile 1 model consists of slate (0.2 - 0.7 km/s), clay (0.8 - 1.3 km/s), and sandy clay (1.4 - 1.9 km/s).While, the model of profile 2 consists of slate (0.5 - 1.0 km/s), clay (1.1 - 1.6 km/ s), and sandy clay (1.7 - 2.5 km/s).The contrasting wave velocity model shows that the SRT method can be used in landslide studies as a reference in determining the mechanism of the landslide system.